Relações entre valores organizacionais e treinamento gerencial: um estudo de caso - Avelino Alexandre Rodrigues da Silva (2004)
This dissertation exams the relationship between organizational values and managerial training and how the trained use their acquired knowledge in the work routine. The choose managerial training program was a MBA course from a respected institution offered for theemployees from Banco de Desenvolvimento de Minas Gerais BDMG. It is supposed that organizational values are capable of affecting the expected results during your planning. Students' perceptions are examined in each hierarchical level, in order to identify the variousforms of organizational values interpretation, assimilation and knowledge application. It was also examined the steps of training, from the elucidation of its need to the evaluation of the reaction to the course. The bank kept these evaluations aiming at the identification of factorsthat affected the transference of training apprenticeship and the insertion of organizational values in this process. A qualitative research was done, utilizing as data collect method the semi-strutured interview. MBA students were interviewed to identify training results and howthe organizational values influence is perceived in the final result. Furthermore, the students filled a quantitative questionnaire with the purpose of identifying the axiological priorities of the organization. The results demonstrated that the managers create profiles of values andmanagerial abilities that must be developed during the training. However, the public sector is too much complex to permit that a MBA course achieve the expected results before passing through a careful process of adaptation from the private sphere to public sphere.